Knowledge and Perceptions of Final-Year Nursing Students Regarding Antimicrobials, Antimicrobial Resistance, and Antimicrobial Stewardship in South Africa: Findings and Implications to Reduce Resistance - Elisma Teague; Selente Bezuidenhout; Johanna C. Meyer; Brian Godman; Deirdré Engler (MDPI AG, 2023)
Antimicrobial resistance (AMR) is being increasingly seen as the next pandemic due to high morbidity and mortality rates, with Sub-Saharan Africa currently having the highest mortality rates driven by high rates of inappropriate prescribing in ambulatory care. In South Africa, nurses typically provide a range of services, including prescribing, in public ambulatory care clinics. However, little is currently known about the perception of final-year nursing students regarding antibiotic use, AMR, and antimicrobial stewardship (AMS). Consequently, we sought to address this important evidence gap. A quantitative descriptive study using a self-administered online questionnaire via Google Forms® was undertaken among six universities in South Africa offering a Baccalaureus of Nursing. Knowledge on the classes of antibiotics, organisms covered, and mechanism of action was lacking. The sample size to achieve a confidence interval of 95% with a 5% error margin was 174, increased to 200 to compensate for possible attrition. Only 15.3% of nurses knew that ceftazidime is not a fourth-generation cephalosporin, and only 16.1% knew that clavulanic acid does not decrease inflammation at the site of infection. In addition, only 58.9% and 67.7% agreed that the prescribing of broad-spectrum antibiotics and poor infection control, respectively, increase AMR. AMS was also not a well-known concept among final-year nurses. The lack of knowledge regarding antibiotics, AMR, and AMS among final-year nurses could have important repercussions in practice once these nurses are qualified. Consequently, this information gap needs to be urgently addressed going forward with updated curricula and post-qualification educational activities to reduce AMR in South Africa